2003
DOI: 10.1152/ajpheart.00853.2002
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine attenuates loss of cardiac sympathetic neurotransmitters produced by congestive heart failure and NE infusion

Abstract: . Desipramine attenuates loss of cardiac sympathetic neurotransmitters produced by congestive heart failure and NE infusion. Am J Physiol Heart Circ Physiol 284: H1729-H1736, 2003. First published January 23, 2003 10.1152/ajpheart. 00853.2002We reported recently that inhibition of neuronal reuptake of norepinephrine (NE) by desipramine prevented the reduction of sympathetic neurotransmitters in the failing right ventricle of right heart failure animals. In this study, we studied whether desipramine also redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
5
11
0
Order By: Relevance
“…TH + nerves are reduced in hearts after CHF, leading to the assumption that the SNS is anatomically denervated (5,(27)(28)(29). Conversely, Liang reported that there was a discrepancy between anatomical integrity and the catecholaminergic properties of the cardiac SNS in CHF, and that nerve fibers expressing the general neuronal marker, protein gene product 9.5, are intact, despite an overall reduction in catecholaminergic neurotransmitters (30). We have previously shown that in the cardiac SNS in CHF, the expression of TH and DBH is downregulated, with concomitant upregulation of GAP43 or PSA-NCAM proteins (6).…”
Section: Discussionmentioning
confidence: 99%
“…TH + nerves are reduced in hearts after CHF, leading to the assumption that the SNS is anatomically denervated (5,(27)(28)(29). Conversely, Liang reported that there was a discrepancy between anatomical integrity and the catecholaminergic properties of the cardiac SNS in CHF, and that nerve fibers expressing the general neuronal marker, protein gene product 9.5, are intact, despite an overall reduction in catecholaminergic neurotransmitters (30). We have previously shown that in the cardiac SNS in CHF, the expression of TH and DBH is downregulated, with concomitant upregulation of GAP43 or PSA-NCAM proteins (6).…”
Section: Discussionmentioning
confidence: 99%
“…Using confocal microscopy, we observed the absence of tyrosine hydroxylase, a well-established marker of sympathetic nerves, in tumor blood vessels visualized by injecting FITC-lectin to the tumor-bearing animals (Fig. 1A); this finding indicates the absence of sympathetic nerves in the blood vessels of these tumors (23)(24)(25)(26). Then, to determine the effect of sympathectomy on the status of DA in these tumor tissues, we measured the concentration of DA in tumor tissues by HLPC with electrochemical detection (27).…”
Section: Loss Of Sympathetic Innervation Of Tumor Blood Vessels Is Asmentioning
confidence: 91%
“…Tyrosine hydroxylase, a rate-limiting enzyme in NE biosynthesis (37), is reduced in heart failure (16,53), which may account, at least in part, for the reduced production of NE. Recently, we observed in several animal models of experimental CHF (23,30,39,41) that the sympathetic nerve profiles as measured by NE histofluorescence and tyrosine hydroxylase immunocytochemistry are reduced in CHF, but there is no significant reduction of protein gene product 9.5 (PGP9.5) (41), a panneuronal marker (20,29,57). Thus the anatomic integrity of the cardiac sympathetic nerves probably is intact in CHF, and the changes of sympathetic neurotransmitters within the nerve endings are caused by functional abnormalities that are potentially reversible with either effective therapy or removal of primary insult that causes heart failure as discontinuation of cardiac pacing in tachycardiainduced cardiomyopathy (30).…”
mentioning
confidence: 99%